(untitled) (Research, Society and Development, 2021)
Objective: To identify and characterize the diagnosed cases of breast cancer in women in the state of Pará in the period from 2013 to 2020. Method: Epidemiological, descriptive, quantitative study, using data from the Painel Oncologia Brasil, from the SUS Department of Informatics. The variables analyzed were: year of diagnosis, age group, therapeutic modality, time to start of treatment and state of diagnosis and treatment. The analysis took place using descriptive statistics in the software Bioestat 5.3. Results: 4,387 cases of breast cancer were diagnosed in the period from 2013 to 2020, with prevalence of 101.22 cases / 100 thousand women in the state. Women between 50 and 59 years of age were more affected by the disease. The treatment was carried out in the form of chemotherapy for 47% of the patients, beginning more than 60 days after diagnosis for the majority. Diagnosis and treatment were carried out in institutions in the state of residence for a significant portion of the sample. Conclusion: Breast cancer is a considerable problem in the state of Pará, affecting a significant number of women. Thus, more studies need to be carried out to identify regional aspects that influence this illness and can support strategic health measures to be taken.